Inducing formation of a corrugated, white-light emitting 2D lead-bromide perovskite via subtle changes in templating cation. Issue 3 (13th December 2019) - Febriansyah, Benny; Giovanni, David; Ramesh, Sankaran; Koh, Teck Ming; Li, Yongxin; Sum, Tze Chien; Mathews, Nripan; England, Jason
Abstract : A corrugated (110)-oriented 2D Pb–Br perovskite was obtained by systematic modulation of templating dication structure. Upon excitation by UV light, this material exhibits intrinsic "cold" white light emission. Abstract : Of a series of new 2D lead-bromide perovskites, templated by closely related dications 1–5, a corrugated (110)-oriented structure was attained only in one, 1 [PbBr4 ]. The others display (100) structures. Upon excitation by UV-light, 1 [PbBr4 ] exhibits intrinsic white-light emission that is "colder" than previously reported for this class of compounds.